Writing in Englishes: Taking Control of the Technology of Power through Literary Aesthetics: A Keynote Speech to the African Studies Association Conference, 2021. (1st March 2023) - Forna, Aminatta
Abstract: As language increasingly becomes uncoupled from the nation state, transnational writers, transnational African writers, and African writers are using language to serve their own purposes and creating new literary aesthetics. This essay, first given as a keynote speech to the 2021 African Studies Association Annual Conference, examines some debates about the relationship between language and power and argues that these are being upended by writers who do not fit conventional categories, including transnational African writers. These writers are exploring the range of options presented by their own multilingualism and making unapologetic aesthetic claims upon the English language.